Localization of plastic deformation during deformation of low‑carbon steel - V. P. Fetisov (Литьë и металлургия)
When controlling the length of the yield site, the influence of the ferrite grain size, the amount of perlite, temperature, speed and deformation scheme on the localization of low‑carbon steel plastic deformation, which reduces the ability of the metal to deformation hardening, is considered.